Drying Shrinkage of Cement Stone with Superplasticizers of Various Chemical Bases - Phan, Ta Van; Nesvetaev, G. V.; Koryanova, Yu. I.; Shut, V. V. (Civil Engineering Journal, 2026)
The crack resistance of reinforced concrete structures also depends on concrete shrinkage. Therefore, assessing the influence of mix design factors and operating conditions on concrete shrinkage is essential to determine the relationships between shrinkage magnitude and kinetics and variables such as ambient humidity, cement properties, and admixture characteristics. These relationships are important for calculating shrinkage crack resistance and, consequently, the durability of reinforced concrete structures. The widespread use of superplasticizers and other mineral additives in concreting, including new complex modifiers, highlights the need to clarify known relationships and identify new dependencies involving the material and mineralogical composition of cements, the properties of admixtures, concrete mix formulation, and environmental humidity on both the magnitude and kinetics of shrinkage deformations. The purpose of this study is to identify patterns in the development of shrinkage deformations of cement paste depending on the type of cement and superplasticizer, including the influence of dehydration degree, and to propose equations that can be used to calculate the shrinkage crack resistance of reinforced concrete structures. The study includes an analysis of established approaches for evaluating changes in drying shrinkage of cement paste as ambient humidity varies. Experimental investigations were conducted on the drying shrinkage of cement paste as a function of evaporable water content and the chemical basis of superplasticizers. The influence of superplasticizers on both the kinetics and magnitude of the basic shrinkage of cement paste is demonstrated, considering evaporable water content under standard conditions as well as after drying to constant mass at 105 °C. The effect of relative air humidity on the basic shrinkage of cement stone has also been clarified. Furthermore, an equation describing the kinetics of shrinkage of cement pastes and a classification of cements based on shrinkage kinetics are proposed. Finally, the dependence of shrinkage for the studied cements with different superplasticizers on relative air humidity is established.